Frontier impact of microRNAs in skeletal muscle research: a future perspective - Aoi, Wataru (Frontiers in Physiology, 2015)
MicroRNAs (miRNAs) are non-coding RNAs that can regulate the expression of mRNAs and proteins by degrading mRNA molecules or by inhibiting their translation. It has been predicted that miRNAs regulate approximately 60% of protein-coding genes that could be involved in a wide range of biological processes. Research over the last 5 years suggests that miRNAs play important roles in skeletal muscle function and several miRNAs have been identified as modulators of myogenesis, muscle mass, and nutrient metabolism in physiological and pathological states. In addition, some miRNAs can be incorporated into intracellular vesicles, released into the circulation, transported to other cells, and possibly function in other organs in an endocrine manner. This phenomenon might explain the interactions between skeletal muscles and other organs. Thus far, several muscle-secreted miRNAs have been identified and their involvement in muscle biology has been debated. Based on the recent understanding, this perspective article describes the potential valuable role of miRNAs in skeletal muscle function, delineates its limitations, and outlines its future perspectives.